The mechanism of creation of a situation of professional and personal development of the future primary school teachers - Olena Yaroshynska (Pedagogical Discourse, 2014)
The article emphasis on the problem of activation the process of professional and personal development and self-development of the future primary school teacher in terms of the educational environment of professional training. Theoretical and practical bases for creating the professional and personal situations of the future elementary school teacher through the mechanism of inclusion the opportunities of the educational environment in the process of becoming the future specialist and the formation of his conscious attitude towards the process of improvement are discovered. The conditions of revealed activation the process of professional and personal development and self-development of the future teacher are founded. The approaches (individual, group, program) to implement the mechanism of creating the situation of professional and personal development of the primary school teachers are submitted. The stages of involving the students in conscious of professional and personal self-development are offered and the possibilities of their implementation in teaching of the course «Fundamentals of pedagogy» are demonstrated. The role of pedagogical support on the stage of personal and professional development of the future elementary school teacher is marked.